The Influence of Electronic Service Quality and Price Perception on Repurchase Intention with Customer Satisfaction as a Mediating Variable (Research on UNIMED Faculty of Economics Students Who Use Spotify) - Dini Vegita Ginting; Ali Fikri Hasibuan (Economic: Journal Economic and Business, 2025)
This study aims to explore the influence of E-Service Quality and Price Perception on Repurchase Intention with Customer Satisfaction as an intervening variable on Spotify users among students of the Faculty of Economics, State University of Medan. The research method used is quantitative with an explanatory research approach. The research respondents numbered 100 students selected using a purposive sampling technique. Data collection was carried out through distributing questionnaires and analyzed using the Partial Least Squares (PLS) method to test the validity, reliability, and relationships between variables in the structural model. The test results show that E-Service Quality has a positive and significant influence on Customer Satisfaction and Repurchase Intention. Price Perception is also proven to have a positive influence on Customer Satisfaction and Repurchase Intention. In addition, Customer Satisfaction acts as a partial mediator in the relationship between E-Service Quality and Price Perception on Repurchase Intention. These findings underscore the importance of improving the quality of digital services and appropriate pricing to strengthen customer satisfaction, thereby encouraging Spotify users to make repeat purchases.